Rapid integration of screen-printed electrodes into thermoplastic organ-on-a-chip devices for real-time monitoring of trans-endothelial electrical resistance. - Kawakita, Satoru; Li, Shaopei; Nguyen, Huu Tuan; Maity, Surjendu; Haghniaz, Reihaneh; Bahari, Jamal; Yu, Ning; Mandal, Kalpana; Bandaru, Praveen; Mou, Lei; Ermis, Menekse; Khalil, Enam; et al. (Biomedical Microdevices, 2023)
Trans-endothelial electrical resistance (TEER) is one of the most widely used indicators to quantify the barrier integrity of endothelial layers. Over the last decade, the integration of TEER sensors into organ-on-a-chip (OOC) platforms has gained increasing interest for its efficient and effective measurement of TEER in OOCs. To date, microfabricated electrodes or direct insertion of wires has been used to integrate TEER sensors into OOCs, with each method having advantages and disadvantages. In this study, we developed a TEER-SPE chip consisting of carbon-based screen-printed electrodes (SPEs) embedded in a poly(methyl methacrylate) (PMMA)-based multi-layered microfluidic device with a porous poly(ethylene terephthalate) membrane in-between. As proof of concept, we demonstrated the successful cultures of hCMEC/D3 cells and the formation of confluent monolayers in the TEER-SPE chip and obtained TEER measurements for 4 days. Additionally, the TEER-SPE chip could detect changes in the barrier integrity due to shear stress or an inflammatory cytokine (i.e., tumor necrosis factor-α). The novel approach enables a low-cost and facile fabrication of carbon-based SPEs on PMMA substrates and the subsequent assembly of PMMA layers for rapid prototyping. Being cost-effective and cleanroom-free, our method lowers the existing logistical and technical barriers presenting itself as another step forward to the broader adoption of OOCs with TEER measurement capability.